Engaging youth in food systems issues: Approaches to youth development and empowerment - Jera E. Niewoehner-Green; Amanda M. Bowling; Kameron Rinehart (Advancements in Agricultural Development)
Food systems issues are inherently interdisciplinary as education, policy, agriculture, and health all play a role in both understanding and solving challenges. Everyone is an actor in the food system, including youth, and encouraging them to become problem-solvers, change agents, and leaders can support a more sustainable food system. To explore how youth are engaging in food systems issues, we interviewed program leaders who include food system topics in their curricula to understand if and how they are empowering youth to engage and address related challenges. Through a collective case study, we identified one convergent theme related to the role of PYD in programming. However, there was more case divergence wherein three themes describe how intentional empowerment approaches support youth development, how youth are viewed and supported as leaders, and in what ways programs are educating about food systems issues. Recommendations include moving past community service to community engagement in food systems issues and conducting research on youth’s perceived ability to address these issues.